O polskich przekładach chorwackiej literatury wojennej — Dragutin Tadijanović: Molba munji nebeskoj / About the Polish translations of the Croatian war writings — Dragutin Tadijanović: Molba munji nebeskoj - Małczak, Leszek (Przekłady Literatur Słowiańskich, 2009)
After 1990 the translations of the Croatian war writings relatively seldom appear in Polish translations of Croatian literature. In the realm of lyrics the translation of Stamać & Sanader‘s book U ovom strašnom času. Antologija hrvatske ratne lirike is the most importanat publication. In this article two translations of Tadijanović‘ poem entitled Molba munji nebeskoj are analysed. The authoress of the first translation Muriel Kordowicz has translated the poem in the above mentioned antology, the author of the second one Julian Kornhauser has published his own translations of Tadijanović‘ poem in the magazine „Literatura na Świecie”. In the recapitulation of this analysis the statement of two different translators‘ strategies is given. The Kordowicz‘ translation is an example of philological model of translation and the Kornhauser‘s translation is an example of transpositional-modulational one.